Neuromuscular fatigue and recovery in elite female soccer: Effects of active recovery - Andersson, H.; Raastad, T.; Nilsson, J.; Paulsen, G.; Garthe, I.; Kadi, F. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To investigate the time course of recovery from neuromuscular fatigue and some biochemical changes between two female soccer matches separated by an active or passive recovery regime.